The Magdalene Laundries in Ireland: making sense through an analysis of Sebastian Barry’s The Secret Scripture - Bonacho, Zoe (Filanderas, 2023)
This essay addresses the transformative power of literature insofar as it is a fundamental tool to learn about experiences suffered by other people. Literature decisively contributes to configuring a palimpsest of veiled stories, affections and ways of life that allow us to better understand our History and to be able to exercise a political function of resistance and resilience. Based on a rigorous textual analysis of Sebastian Barry’s novel The Secret Scripture (2008), as well as some narratological strategies, the use of analepsis and a noticeable fragmented narrative, this methodological approach will be complemented with the use of other theoretical frameworks such as feminist studies, affect studies and vulnerability studies. The main aim of this essay will focus on revealing the intertextual codes inscribed in the personal conscience by Irish culture and society, which led to the confinement and punishment of all those women who did not adjust to their role as wives and mothers within marriage, depriving them of their lives and their children. Although such an experience is a traumatic event in itself, this dissertation will mainly focus on how Barry’s work entails a political commitment that implies a redefinition of the traditional concept of vulnerability.